Malaria knowledge, attitude, and practice among communities involved in a seasonal malaria chemoprevention study in Nanyumbu and Masasi districts, Tanzania - Ngasala, Billy; Mwaiswelo, Richard O.; Chacky, Frank; Molteni, Fabrizio; Mohamed, Ally; Lazaro, Samwel; Samuel, Bushukatale; Mmbando, Bruno P. (Frontiers in Public Health, 2023)
Background: This study assessed malaria knowledge, attitudes, and practices on malaria infection and interventions in Masasi and Nanyumbu districts, Tanzania. Methods: A community-based cross-sectional survey was conducted between August and September 2020, among the heads of households having at least one under-five child. Information on knowledge, attitudes and practices on malaria infection and interventions was gathered from the heads of the households using a structured questionnaire. The knowledge level was classified into low, moderate, and high. Attitudes were classified into positive and negative, whereas practices were classified into good and poor. Children aged between 3 and 59 months were screened for malaria infection using malaria rapid diagnostic test (mRDT). The proportion of the households’ heads with high levels of knowledge was the primary outcome. Results: A total of 1556 household heads were interviewed, 1167 (75.00 %) were male, and according to marital status, 1067 (68.57 %) were couples. All the household heads had some knowledge of malaria, but 47.33 % (736/1555) and 13.83 % (215/1555) of them had moderate and high knowledge, respectively. The level of knowledge on malaria was significantly influenced by gender (adjusted odds ratio [aOR]=0.72, 95.00 % confidence interval [CI]=0.56-0.94, p=0.017), level of education (aOR=1.50, 95.00 % CI=1.04-2.16, p=0.03), and the occupation of the household head (aOR=1.90, 95.00 % CI=1.22-2.96, p=0.004). Majority of the households (83.87 % (1305/1556) had bed nets hanging on the sleeping spaces. Of the household heads possessing bed nets, 85.10 % (514/604), 79.62 % (586/736), and 95.35 % (205/215) of them had a low, moderate, and high level of knowledge of malaria infection, respectively, (trend x2=31.53, p<0.001). The majority (95.04 % (1474/1551) of the household heads perceived sleeping under the bed net to be beneficial. Furthermore, 15.56 % (94/604), 14.67 % (108/736), and 7.44 % (16/215) of the household heads with low, moderate, and high knowledge, respectively, had children with malaria infection, (trend x2=9.172, p=0.01). Conclusion: The study population had a good level of knowledge about malaria infection, and a good attitude toward malaria interventions and the majority of them were using bed nets.